KEPUASAN MAHASISWA TERHADAP FASILITAS GEDUNG AUDITORIUM GRAHA TANOTO DI UBHARA JAYA - Muhammad Abbas Adika; Farrel Ihsan, Andhika Maulana, Rijal Anjani, Dwi Hardiyana Saputra, Fajar Muhammad (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The obligation of an agency in attracting the attention of visitors or enthusiasts is to build a building with good facilities and good quality. The auditorium building of graha tanoto ubhara jaya is one of them, the increasing number of visitors to this building, which will certainly require more workers in the building to serve, not only to serve, but the agency also needs to provide adequate facilities to increase satisfaction with its students. To find out how satisfied students are with campus facilities, this study will use three tests: K-S normality test, homogeneity test, and linearity test. These three tests can show that the population that is satisfied with campus facilities is normal and related to each other. Thus, it can be concluded that the facilities provided by Ubhara Jaya for the development of Graha Tanoto Auditorium Building have an interrelated influence.